2011
DOI: 10.1038/bmt.2011.13
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic impact of iron parameters in patients undergoing allo-SCT

Abstract: Iron overload contributes to increased transplant-related mortality, and serum ferritin is typically used to detect iron overload. Other iron parameters have received limited attention. We studied serum ferritin, transferrin, transferrin saturation, iron, soluble transferrin receptor (sTfR) and C-reactive protein (CRP) levels in 230 consecutive patients undergoing myeloablative allo-SCT. All iron parameters were significantly associated with survival. When analyzed individually, both sTfR and transferrin satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 14 publications
3
27
5
Order By: Relevance
“…The details of the 4 cohorts and the 276 patients included in this analysis have been previously published 4,14,15,22 . The median age was 52 (range, 18–74) years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the 4 cohorts and the 276 patients included in this analysis have been previously published 4,14,15,22 . The median age was 52 (range, 18–74) years.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, because ferritin is an acute phase reactant, its elevation in serum may betray inflammatory states including active infection or more advanced disease status, which are expected to confer an adverse prognosis in HCT independent of iron overload. There are at present 4 published studies that have directly assessed the impact of pre-HCT LIC on outcome, but differ in their conclusion despite their generally similar design 4,14,15,22 . We therefore undertook an individual patient data meta-analysis of all 4 studies, with the aim of clarifying whether pre-HCT LIC is, like SF, associated with worse OS or NRM.…”
Section: Introductionmentioning
confidence: 99%
“…Ferritin is a well-known indicator of the body's iron store and has various activities, such as that of an acute phase reactant, antioxidant, or growth factor for AML cell lines 2223. Hyperferritinemia is a poor risk factor in patients with hematologic malignancies, probably because of the adverse impact of body iron accumulation in transfusion-dependent patients 24252627. However, hyperferritinemia might also affect prognosis through mechanisms other than iron accumulation, because several studies have demonstrated that even patients with hyperferritinemia at diagnosis without prior transfusion have poor prognosis 2829.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that high pre-transplantation ferritin levels were strongly associated with greater risk of relapse and lower overall survival [2][3][4][5]. In these patients, hyperferritinemia is mainly due to transfusion relatediron overload [6].…”
Section: Introductionmentioning
confidence: 99%